2014
DOI: 10.1103/physreve.89.063005
|View full text |Cite
|
Sign up to set email alerts
|

Electro-osmotic flow along superhydrophobic surfaces with embedded electrodes

Abstract: The effect of the secondary fluid enclosed in the indentations of a superhydrophobic surface on electro-osmotic flow is investigated. We derive analytical expressions for the net electro-osmotic flow over periodically structured surfaces, accounting for the influence of dissipation within the secondary fluid as well as for the role of charges at the fluid-fluid interfaces that are generated by auxiliary electrodes. Specifically, for a surface with rectangular grooves, the electro-osmotic flow velocity is relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…It has been suggested that superhydrophobic surfaces can be employed as a means for pumping liquid in conjunction with thermocapillary flow due to a temperature gradient along the gas–liquid interface (Baier, Steffes & Hardt 2010), diffusioosmotic flow (Huang et al. 2008) or electroosmotic flow (Squires 2008; Belyaev & Vinogradova 2011; Steffes, Baier & Hardt 2011; Schönecker & Hardt 2014). It should be interesting to extend the results of the present paper to such situations in order to study the impact of surfactants in these cases.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that superhydrophobic surfaces can be employed as a means for pumping liquid in conjunction with thermocapillary flow due to a temperature gradient along the gas–liquid interface (Baier, Steffes & Hardt 2010), diffusioosmotic flow (Huang et al. 2008) or electroosmotic flow (Squires 2008; Belyaev & Vinogradova 2011; Steffes, Baier & Hardt 2011; Schönecker & Hardt 2014). It should be interesting to extend the results of the present paper to such situations in order to study the impact of surfactants in these cases.…”
Section: Discussionmentioning
confidence: 99%
“…The application of the reciprocal theorem (2.16) to a number of problems involving the motion of particles in low Reynolds number flows has been reviewed by Leal (1980); for several more recent applications, see Stone & Samuel (1996), Masoud & Stone (2014) and Schönecker & Hardt (2014). Its use in the present study is inspired by the works of Brenner (1964) and Stone & Samuel (1996).…”
Section: Introductionmentioning
confidence: 92%
“…where Σ comprises the particle surface Σ p (outer normal vector n = −e r ) and the surface Σ ∞ at infinity (outer normal vector n = e r ). The Lorentz theorem (3.2) has been exploited in a number of cases, for instance by Stone & Samuel (1996), Masoud &Stone (2014), andSchönecker &. Its use in the present study is inspired by the argumentation of Stone & Samuel (1996).…”
Section: Applying the Lorentz Reciprocity Theoremmentioning
confidence: 99%
“…The hydrodynamic slip length of the hydrophobic surface is an intrinsic hypothetical parameter that refers to the length below the wall where the fluid velocity extrapolates to zero . It is important to note that the synthesized engineered surface coated with hydrophobic octadecyltrichlorosilane possesses hydrophobicity and for such surfaces, a large slip length of the order of micrometer can be achieved. , The impact of the hydrodynamic slippage on the EOF has been studied by several researchers. However, all of the previously listed investigations are conducted by considering the background electrolyte Newtonian in nature. It is noteworthy to mention that numerous biomicrofluidic applications involve fluidic media like bioliquids (e.g., blood, DNA, protein solutions), polymeric solutions, worm-like micellar solutions, colloidal suspensions, and others.…”
Section: Introductionmentioning
confidence: 99%